Typing of Staphylococcus aureus by PCR for DNA sequences flanked by transposon Tn916 target region and ribosomal binding site. - Cuny, C (1996)
The continuous intra- and interhospital spread of multiresistant Staphylococcus aureus demands a rapid molecular typing system. This study describes the fingerprinting of S. aureus by PCR amplification of DNA sequences flanked by the target site for transposon Tn916 and the ribosomal binding site and neighboring nucleotides (target 916-Shine-Dalgarno PCR [tar 916-shida PCR]). Both starting points for PCR are known to be randomly distributed on the S. aureus chromosome. By use of SmaI-macrorestriction patterns as the reference method it was shown that this PCR genotyping discriminates among strains of the major clonal groups of the species S. aureus (strains with phage patterns 29, +, 94, 96, and 95 as well as group II and group III patterns) and identifies the six epidemic methicillin-resistant S. aureus strains prevalent in German hospitals. All of the investigated strains including methicillin-sensitive. S. aureus were typeable. Tar 916-shida patterns are stable during the dissemination of epidemic methicillin-resistant S. aureus among different hospitals.